2023
DOI: 10.1038/s41598-023-39442-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rutin and its combination with metformin on vascular functions in type 1 diabetes

Abstract: The present work examined the effect of oral administration of rutin and its combination with metformin, an antidiabetic drug on blood glucose, total cholesterol and triglycerides level and vascular function in streptozotocin (STZ) -induced diabetic rats. Male Sprague Dawley rats were rendered diabetic by a single intraperitoneal injection of STZ (50 mg/kg). Rutin and metformin were orally administered to diabetic rats at a dose of 100 mg/kg and 300 mg/kg body weight/day, respectively, for 4 weeks. Plasma anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The results indicated that treatment with compound 19 caused a decline in blood glucose levels in STZ-induced diabetic rats at various time intervals. Metformin was taken as a positive control and tested at a reported dose of 300 mg/kg. The data indicate that compound 19 exerted a significant decrease in blood glucose levels with a percent decrease of around 21.6% ( P < 0.01) after 5 h of treatment in STZ-induced diabetic rats, at an arbitrary dose of 100 mg/kg of body weight. However, treatment with metformin at 300 mg/kg demonstrated a 61.9% ( p < 0.001) reduction in the blood glucose level of STZ-induced diabetic rats after 5 h. Importantly, the biological effect of compound 19 seemed to be modest in comparison to metformin.…”
Section: In Vivo Antihyperglycemic Activity Of Compound 19 In Stz-ind...mentioning
confidence: 99%
“…The results indicated that treatment with compound 19 caused a decline in blood glucose levels in STZ-induced diabetic rats at various time intervals. Metformin was taken as a positive control and tested at a reported dose of 300 mg/kg. The data indicate that compound 19 exerted a significant decrease in blood glucose levels with a percent decrease of around 21.6% ( P < 0.01) after 5 h of treatment in STZ-induced diabetic rats, at an arbitrary dose of 100 mg/kg of body weight. However, treatment with metformin at 300 mg/kg demonstrated a 61.9% ( p < 0.001) reduction in the blood glucose level of STZ-induced diabetic rats after 5 h. Importantly, the biological effect of compound 19 seemed to be modest in comparison to metformin.…”
Section: In Vivo Antihyperglycemic Activity Of Compound 19 In Stz-ind...mentioning
confidence: 99%